Practical methods for optimal control using nonlinear programming - Betts, John T. 1943- (Society for Industrial and Applied Mathematics, 2020)
"The third edition focuses on the direct transcription method for optimal control and includes new material on implicit Runge-Kutta discretization techniques, new chapters on partial differential equations and delay equations, and over seventy test problems and open source FORTRAN code for all of the problems"--
Revised edition of: Practical methods for optimal control and estimation using nonlinear programming. 2nd ed. ©2010
Includes bibliographical references and index
Keywords: Optimale Kontrolle; Nichtlineare Optimierung; Control theory; Mathematical optimization; Nonlinear programming